New records of fairy shrimp (Anostraca, Branchinectidae) in temporary wetlands from Patagonia - García, Roberto Daniel (2023)
Despite its widely distribution in pools or hypersaline lakes of Argentina, the anostracans are among the least known of all faunal elements in temporary aquatic environments. In this study we show new records of Branchinecta vuriloche for Patagonia, collected in two isolated forested temporary wetlands.